Implementasi Indonesia National Single Window (INSW) dalam Upaya Kelancaran Pengurusan Dokumen Impor di PT. Cahaya Moda Indonesia - Winarni, Endra; Wintia, Ema (PPPM Polimarin, 2023)
The existence of the Indonesia National Single Window (INSW) application system for import activities is very helpful to be faster and more efficient in terms of time, cost, and information. This research aims to determine the comparison before and after the implementation of INSW, the role of INSW, the obstacles that are often faced after the implementation of INSW and the solutions provided. This research is a qualitative research with descriptive method. The object of research is the operation of PT. Cahaya Moda Indonesia. The results of the research state that every process of completing the issuance of mandatory import documents goes through the INSW system service procedure, so that the issuance of the Surat Persetujuan Pengeluaran Barang (SPPB) is faster. The obstacles that occur are the refusal by Customs when submitting the document because there is a mismatch between the document and INSW input, as well as the many steps that must be completed in filling out this system and frequent internet disturbances. Efforts are being made, namely training and evaluating employees to understand the INSW system. As well as providing Wifi for the smooth operation of the INSW system